School functioning of a child with chronic disease - Łukasik, Renata; Waksmańska, Wioletta; Woś, Halina (Nursing Problems / Problemy Pielęgniarstwa, 2013)
Background. Doctors specialising in various disciplines report a growing problem of chronic diseases in children and youths. The diseases affect the functioning of the young people at their homes and at school. The problem of a chronic disease in a child is more complex than in the case of adults as the ailments overlap the psychophysical development of a child during their kindergarten and school education, which in consequence affects the selection of further education and interests. The awareness of a chronically ill child functioning at school is important for teachers, parents and school nurses. Aim. The objective of the paper is to present the main psychophysical and social problems related to school education of a chronically ill child and indication of the methods of the child support and assistance in order to enable the child to achieve the best educational results. Conclusions . In common schools there are more and more children suffering of chronic diseases. A chronic disease affects the child’s psychophysical, emotional and intellectual development and, in consequence, the functioning of the child as a student — this makes the teachers face new challenges. The task of the teachers is to provide the chronically ill children with the best conditions for learning by virtue of proper organisation of the educational process, as well as application of the methods and forms of teaching adequate to the psychophysical capability of an ill child. The duties of a teacher and nurse in reference to a chronically ill child are regulated by the legal acts.